Energy Balance Control for Improving Transient Performance of DC Bus Voltage in Power Electronic Transformer for the Voltage-Sensitive Loads - Gaohui Feng (Energies, 2022)
The power electronic transformer (PET), as a main topology for the energy router in the energy internet, consists of the rectifiers, the dual active bridge (DAB), and the inverter, and these three parts are connected by two dc buses. So, the performance of the dc bus voltages is very important because it can totally affect the output waveforms of the dc and ac voltage, especially for the voltage-sensitive loads. Compared with the proportion integration (PI) control scheme, the energy control method utilizes the energy as the control variable, and the control strategy derived from the energy relationship, including the passive elements and all the interfaces, is more direct and explicit. In this paper, considering the energy between the dc bus capacitors and the input inductor and the load and the source in the PET topology, the energy balance control (EBC) strategy is proposed. For the two dc bus voltages, the energy balance relationship of the different time scales is used to decouple the interaction in the control scheme. The EBC strategy can obviously reduce the fluctuation and the transient time of the two dc bus voltages when the load power or voltage reference is changed. Thus, under the limited voltage fluctuation, the EBC strategy can reduce the dc bus capacitance in order to reduce the volume and weight of the converter and enhance the reliability. The simulation and experimental results verify the effectiveness of the proposed control strategy.